A homozygous splice variant in ATP5PO, disrupts mitochondrial complex V function and causes Leigh syndrome in two unrelated families. Issue 5 (11th July 2022) - Ganapathi, Mythily; Friocourt, Gaelle; Gueguen, Naig; Friederich, Marisa W.; Le Gac, Gerald; Okur, Volkan; Loaëc, Nadège; Ludwig, Thomas; Ka, Chandran; Tanji, Kurenai; Marcorelles, Pascale; Theodorou, Evangelos; et al.
Abstract: Mitochondrial complex V plays an important role in oxidative phosphorylation by catalyzing the generation of ATP. Most complex V subunits are nuclear encoded and not yet associated with recognized Mendelian disorders. Using exome sequencing, we identified a rare homozygous splice variant (c.87+3A>G) in ATP5PO, the complex V subunit which encodes the oligomycin sensitivity conferring protein, in three individuals from two unrelated families, with clinical suspicion of a mitochondrial disorder. These individuals had a similar, severe infantile and often lethal multi‐systemic disorder that included hypotonia, developmental delay, hypertrophic cardiomyopathy, progressive epileptic encephalopathy, progressive cerebral atrophy, and white matter abnormalities on brain MRI consistent with Leigh syndrome. cDNA studies showed a predominant shortened transcript with skipping of exon 2 and low levels of the normal full‐length transcript. Fibroblasts from the affected individuals demonstrated decreased ATP5PO protein, defective assembly of complex V with markedly reduced amounts of peripheral stalk proteins, and complex V hydrolytic activity. Further, expression of human ATP5PO cDNA without exon 2 (h ATP5PO ‐∆ex2) in yeast cells deleted for yATP5 ( ATP5PO homolog) was unable to rescue growth on media which requires oxidative phosphorylation when compared to the wild type construct (h ATP5PO ‐WT), indicating that exon 2 deletion leads to a non‐functional protein. Collectively, our findings support the pathogenicity of the ATP5PO c.87+3A>G variant, which significantly reduces but does not eliminate complex V activity. These data along with the recent report of an affected individual with ATP5PO variants, add to the evidence that rare biallelic variants in ATP5PO result in defective complex V assembly, function and are associated with Leigh syndrome.